The Influence of Weblog Media on Increasing Learning Outcomes and Responses Using the Problem Based Learning Model in Buffer Solution Material at SMAN 18 Medan - Anna Juniar; Natasya Laura Marpaung (Eduvest - Journal of Universal Studies, 2024)
Lack of media utilization during the learning process can lead to low student learning outcomes. This study aims (1) to determine the effect of increasing higher learning outcomes using weblog media using the Problem Based Learning model rather than using powerpoint; (2) to determine the response to the use of weblog media using the Problem Based Learning model; (3) to determine the positive correlation between response and increased learning outcomes. The sampling technique is purposive sampling. Hypothesis testing was carried out using the right one-party t-test, the results of the study at the significance level = 0.05 showed that tcount > ttable (5.95 > 1.99) so there was an effect of increasing learning outcomes higher using weblog media than using powerpoint. The increase in student learning outcomes of the experimental class was 78.28% and the control class was 52.45%. The response to the weblog media with the Problem Based Learning model was 75.5% in the interesting category. The correlation test of the response to the improvement of student learning outcomes shows rcount> rtable (0.58> 0.27) so there is a positive and significant correlation between the response and the improvement of learning outcomes.